KONSELING MOTIVASI TERHADAP ORANG TUA PASIEN PENDERITA KANKER PAYUDARA (Studi terhadap Konselor RSU Aisyiyah Muhammadiyah Kota Padang) - Ahmad Putra Putra; Meri Susanti Meri (Universitas Islam Negeri Imam Bonjol Padang, 2020)
ABSTRACTThis paper explains about the implementation of motivational counseling by counselors at Aisyiyah Public Hospital in Padang to parents of patients with breast cancer. Cancer is one of the deadly diseases and no one wants to get cancer, one of them is breast cancer. So, anxiety, hopelessness and fear not only in patients, but the patient’s parents are also shaken when their children develop breast cancer. This study uses a qualitative approach with qualitative descriptive analysis. The results obtained are that through motivational counseling, the patient's parents feel enlightened, increase optimism, sincerity and giving maximum attention to children such as praying for and supporting children’s recovery. Motivation counseling is considered to have a good and effective effect in providing calm to the anxiety and frustration of the parents towards the patient’s recovery.